2012
DOI: 10.1016/j.applanim.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Behavioural Assessment of Angus steers during pre-slaughter handling and relationship with temperament and physiological responses

Abstract: This study examined the behavioural expression of cattle immediately prior to slaughter through the process of Qualitative Behavioural Assessment (QBA), and compared these results to measurements of physiology and temperament. Twenty-eight Angus steers were filmed while in a funnel chute as they were being moved towards an abattoir killing box.Footage of cattle was shown in random order to 15 observers. Observers assessed the cattle using a qualitative approach based on Free Choice Profiling (FCP) methodology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 35 publications
(43 reference statements)
3
28
1
3
Order By: Relevance
“…A growing body of empirical evidence acquired from studies employing the methodology of qualitative behavioural assessment indicates that aspects of the animal's demeanour are indicative of affective state Rousing and Wemelsfelder 2006;Brscic et al 2009;Stockman et al 2011Stockman et al , 2012Napolitano et al 2012;Rutherford et al 2012). Wechsler and Lea (2007) have suggested that speed with which the animal learns to respond to new environmental cues is an overlooked indicator of cognitive ability and adaptation by learning in farm animals.…”
Section: Defining the Phenotypementioning
confidence: 99%
“…A growing body of empirical evidence acquired from studies employing the methodology of qualitative behavioural assessment indicates that aspects of the animal's demeanour are indicative of affective state Rousing and Wemelsfelder 2006;Brscic et al 2009;Stockman et al 2011Stockman et al , 2012Napolitano et al 2012;Rutherford et al 2012). Wechsler and Lea (2007) have suggested that speed with which the animal learns to respond to new environmental cues is an overlooked indicator of cognitive ability and adaptation by learning in farm animals.…”
Section: Defining the Phenotypementioning
confidence: 99%
“…A field study was designed to attempt to validate the marketing claims made by the proponents of the product by measuring the impacts of feeding winery by-products on beef cattle flight speed (FS), a quantitative behavioural assessment tool which has been widely used as a measure of beef cattle temperament and has been correlated with weight gain in cattle (Muller & von Keyserlingk, 2006;Petherick et al, 2009;Schwartzkopf-Genswein et al, 2012;Stockman et al, 2012). After animal weights were recorded and cattle ID was determined via Radio-Frequency identification tags (RFID) tags, the flight speed of cattle was evaluated.…”
Section: Flight Speedmentioning
confidence: 99%
“…In detailed reviews the value of observer assessments (when used in careful experimental design) in investigating animal welfare are described (Wemelsfelder 1997;Meagher 2009). Of particular interest are studies correlating human assessment of an animal's emotional experience with physical and physiological measures of stress in animals (Minero et al 2009;Stockman et al 2012), inferring some verisimilitude in human assessment of animals' emotional experiences.…”
mentioning
confidence: 99%